The externalities of solid fuel CO2 emissions on rice production: A time series analysis for Pakistan - Mushtaq, Mansoor; Malik, Arshad Mahmood; Hameed, Gulnaz (Economic Journal of Emerging Markets, 2023)
Purpose ― This study examines the externalities of CO2 emissions from solid fuel consumption on rice production in Pakistan using time series data from 1984 to 2021. Methods ― The independent variables include CO2 emissions from solid fuel consumption, cultivated area, agricultural equipment, tube wells, and improved seed, whereas the dependent variable is rice production. A robust analysis was done by altering the solid fuel CO2 emissions proxy. The empirical study used the vector error correction model and Johansen's cointegration test.Findings ― Solid fuel CO2 emissions negatively and significantly impact rice production, implying that solid fuel CO2 emissions decrease rice production. Tube wells have a negative and significant influence on rice production. Conversely, cropped land, agricultural machinery, and improved seeds boosted rice production. The results remained robust even when the proxy for solid fuel CO2 emissions was changed. Implications ― The study recommends developing regulations to limit solid fuel CO2 emissions to prevent environmental degradation and increase rice production. To boost rice production, more land should be farmed, agricultural machinery should be employed, and improved seeds should be used.Originality ― This study is the first to examine the impact of CO2 emissions from solid fuel consumption on rice production in Pakistan